A SITUAÇÃO SOCIOECONÔMICA E O CONSUMO DE AÇÚCARES PODEM EXPLICAR A ASSOCIAÇÃO ENTRE DEPRESSÃO E CÁRIE EM ADOLESCENTES? UM ESTUDO DE BASE POPULACIONAL, SÃO LUÍS - NOGUEIRA FILHO, Ronaldo (2024)
Depression is the second leading cause of death in people aged 15 to 29 worldwide and its association with other physical Non-communicable diseases (NCDs) appears to occur in a bidirectional sense, as social determinants of poverty that act on depression increase the risk of developing other NCDs and the drugs used to treat NCDs can worsen psychiatric symptoms, especially in adulthood. Caries is a highly prevalent NCD globally and is also explained by poverty, and the high consumption of foods rich in added sugars plays a crucial role in the etiology of the disease. Furthermore, the consumption of sugar is related to mental disorders, which may be associated to several mechanisms that range from bodily inflammation generated by hyperglycemia to neurobiological changes that can cause substance-related reward disorder. Thus, considering that adolescence constitutes a window of opportunities for consolidating habits that can continue throughout life and that caries and depression are NCDs that share common risk factors, we hypothesize that there is a correlation between these two diseases, triggered by their common risk factors, such as sugar consumption and socioeconomic status. The objective of this research was to evaluate the correlation between caries and depression, analyzing paths that go from the socioeconomic situation and sugar consumption in a population sample of adolescents. This is a cross-sectional study nested within a birth cohort belonging to the RPS cohort consortium, involving follow-up with adolescents between 18 and 19 years old (n=2515), who were born in 1997/1998 in the city of São Luís, Maranhão, Brazil. The theoretical model explored caries and depression as outcomes, as well as the explanatory variables: Socioeconomic situation and consumption of added sugars. Furthermore, the correlation between caries and depression was considered in the model. The latent variable Socioeconomic Situation was deduced from the variance shared between the education level of the head of the family and the adolescent, monthly family income and economic class. The consumption of added sugars was formed by the sum of added sugar consumption in g/day. The diagnosis of depression was measured using the Mini International Neuropsychiatric Interview Questionnaire - M.I.N.I. Caries was analyzed by the number of decayed, missing and filled teeth- DMFT Index, according to the World Health Organization (WHO). The worst socioeconomic situation has increased sugar consumption (SC= 0.05; p <0.001) and depression (SC= 0.088; p= 0.013). Sugar consumption had a direct effect on both depression (SC= 0.075; p= 0.024) and tooth decay (SC= 0.049; p= 0.016), in addition to an indirect effect on caries via Visible Plate Index (VPI) (CP= 0.007; p=0.016). DMFT and depression were correlated with each other (SC= 0.068; p= 0.041). Our findings suggest that there is a association between caries and depression in adolescents, explained by common risk factors such as lower socioeconomic status and higher sugar consumption, which can explain the co-occurrence of these two conditions in adolescents. Therefore, efforts to reduce the burden of chronic diseases such as tooth decay and depression must begin early in life and target common risk factors.